The Implication of Positive Reinforcement Strategy in dealing with Disruptive Behaviour in the Classroom: A Scoping Review - Aisha Rafi , Ambreen Ansar , Muneeza Amir Sami, (Journal of Rawalpindi Medical College, 2020)
The scoping review study was carried out from January 18, 2019, to February 18, 2019, by following the Arksey and O'Malley method of scoping review. An extensive search in the bibliographic databases, PubMed, ERIC, and Google scholar for the gray literature was done. The search was narrowed by a set of inclusion and exclusion criteria. The studies included in the literature search were sort by the PRISMA flow chart. The selected studies address the use of a positive reinforcement strategy to manage disruptive behavior in the classroom. The positive reinforcement strategies identified were praise (41%), feedback (33%), and other classroom management studies (25%). Skinner's operant learning principle has a classroom implication for increasing the likelihood of the desired behavior. The results of the review can be used to implement evidence-based practice and policy regarding improving the desired behavior in the classroom.